2021
DOI: 10.52214/cjgl.v41i1.8838
|View full text |Cite
|
Sign up to set email alerts
|

“Do We Not Bleed?” Sanitation, Menstrual Management, and Homelessness in the Time of COVID

Abstract: Although access to adequate sanitation is formally recognized as a basic human right, public toilets have long been flagged as absent necessities by groups marginalized by class, gender, race, and ability in the United States. Navigating public spaces without the guarantee of reliable restrooms is more than a passing inconvenience for anyone needing immediate relief. This includes workers outside of traditional offices, people with medical conditions, caretakers of young children, or anyon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…As Perri et al (2020) suggest, added stress as a result of the limited access to essential resources and services could lead to a decline in the mental and physical health of PEH and increase their risk of alcohol and drug use, emphasizing an important area for further consideration. In addition, limited access to WASH facilities can pose challenges for women and all those who menstruate to take care of their menstrual needs in a private and dignified matter (Teizazu et al, 2021). In our study, some women reported not having access to a private space in which to take care of their menstrual needs.…”
Section: Discussionmentioning
confidence: 69%
“…As Perri et al (2020) suggest, added stress as a result of the limited access to essential resources and services could lead to a decline in the mental and physical health of PEH and increase their risk of alcohol and drug use, emphasizing an important area for further consideration. In addition, limited access to WASH facilities can pose challenges for women and all those who menstruate to take care of their menstrual needs in a private and dignified matter (Teizazu et al, 2021). In our study, some women reported not having access to a private space in which to take care of their menstrual needs.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, income loss during the COVID-19 pandemic has been associated with menstrual product insecurity [ 34 ]. COVID-19 may thereby perpetuate existing economic disparities and negatively impact women’s menstrual experiences and quality of life [ 35 37 ]. To fully understand reproductive health during the COVID-19 pandemic, it is critical to identify factors related to menstrual irregularities in a sample that includes women from historically marginalized racial and ethnic groups.…”
Section: Introductionmentioning
confidence: 99%